Investigating Mentors' Perceptions Of The Effectiveness Of Using Resiliency-Building Strategies Within An At-Risk Adolescent Intervention Program - Dzoba, Nicholas (2014)
This research study seeks to enhance previous mentoring literature (Converse & Lignugaris, 2008; Cavell, Elledge, Malcolm, & Faith, 2009; Devenport & Lane, 2009) by further identifying the strategies and skills which help mentors form quality relationships and ultimately impact the resilience of at-risk adolescent mentees. Specifically, this study investigates volunteer mentors’ perceptions of incorporating the positive coping strategies of active listening, emotional regulation, conflict resolution, and future orientation within the initial stages of the mentoring process. Participants in this study are divided into two groups: the Coping Strategies (CS) Group and the Untrained Group (UG). The CS Group mentors have been individually trained to use the aforementioned coping strategies prior to being matched with mentees. The Untrained Group consists of mentors who received no formal training. Semi-structured interviews, which were conducted between three and four months into each mentoring relationship, reveal that focusing on relationship building and creating a level of comfort and trust with mentees were viewed by mentors from both groups as the paramount objectives during these beginning stages. Active listening is identified by a majority of participants as crucial for establishing a connection between mentor and mentee, building trust within the relationship, and engendering meaningful dialogue during beginning mentor sessions. Ultimately, this study finds that active listening training can be useful for helping mentors establish the foundation for a quality mentoring relationship, as well as for the use of additional coping strategies